Determinan Non-Performing Financing pada Bank Pembiayaan Rakyat Syariah di Indonesia - Surepno Surepno; Sofi Nur Azmi; Dian Pujiatma Vera Subchanifa (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study aims to empirically test the determinants or factors that affect Non-Performing Finance (NPF) in Islamic Finance Banks (BPRS) in Indonesia. The determinants analyzed are internal and external factors. Internal factors consist of the Capital Adequacy Ratio (CAR), Financing to Deposits Ratio (FDR), and Operating Costs for Operating Income (BOPO). Meanwhile, external factors are Inflation, Exchange Rate, and Interest Rate (BI Rate). Method: This study uses a quantitative approach. The research data is secondary data obtained from the websites of the Financial Prosecutor Authority (OJK) and Bank Indonesia (BI). The data collection technique is through time series data collection from 2013 to 2020. As for data analysis using multiple linear regression analysis.Results: Based on the results of the study showed that simultaneously internal and external factors had an effect on Non-Performing Finance. While partially that internal factors, namely CAR, FDR and BOPO have a positive and significant effect on the NPF. On external factors, the exchange rate variable partially has a positive and significant effect on the NPF, while the BI Rate has a negative and significant effect on the NPF, but the inflation variable partially has no significant effect on the NPF.Implications: This research can be used as material for consideration by BPRS to be more careful in channeling financing to customers. In addition to paying attention to the internal financial condition of the BPRS, it must also be aware of factors outside the BPRS, such as the exchange rate and the BI rate because they can also have an impact on financing.Novelty: This research builds on previous research by adding different variables in terms of financial performance and macroeconomic factors.